MitraClip intervention for Sheehan syndrome complicated by dilated cardiomyopathy and valvular insufficiency: a case report and literature review - Yan, Liu; Wujin, He; Hairong, Wang; Mei, Zhou; Farong, Liao; Wei, Yu; Qi, Zhang (Frontiers in Endocrinology, 2025)
IntroductionSheehan syndrome (SS) is a form of hypopituitarism caused by severe postpartum hemorrhage. It leads to premature dysfunction of the target organs affected by various hormone deficiencies, resulting in a range of clinical manifestations. The coexistence of SS and dilated cardiomyopathy is rare, and symptomatic treatment remains the main treatment approach. Here, we describe a case in which a MitraClip procedure was used to treat SS-associated cardiac insufficiency.Case reportA 50-year-old woman with a history of SS and dilated cardiomyopathy was admitted to the hospital owing to worsening shortness of breath for one month, which had aggravated over the past day. Her laboratory findings were as follows: potassium 5.92 mmol/L, chloride 96.56 mmol/L, magnesium 1.08 mmol/L, triiodothyronine 0.69 nmol/L, free thyrogenic ammonia 2.44 pmol/L, and B-type natriuretic peptide precursor 23,904 pg/mL. Medical imaging revealed left atrial and left ventricular enlargement (left atrial size 39 mm, left ventricular diameter 52 mm); severe regurgitation of the second and tricuspid valves; bilateral pleural effusion; abdominal, pelvic, and pericardial effusion Despite repeated pharmacological treatment, the patient’s condition did not improve. Finally, she underwent atrial septal puncture followed by percutaneous mitral valve repair using a MitraClip. The left Atrial diameter (LAS) decreased from 39mm (pre-intervention) to 34mm (pre-discharge), and decreased to 24mm during the 9-month outpatient follow-up. The left ventricular ejection fraction (LVEF) increased from 31% (pre-intervention) to 46% during the 9-month outpatient follow-up, and the pulmonary artery systolic pressure (PASP) decreased from 52 mmHg (pre-intervention) to 26 mmHg during the 9-month outpatient follow-up.ConclusionThe coexistence of Sheehan syndrome and dilated cardiomyopathy is rare. MitraClip intervention may be considered to treat severe mitral valve regurgitation due to dilated cardiomyopathy induced by Sheehan syndrome in cases where medical therapy is ineffective and the patient has significant symptoms of heart failure.